PELAKSANAAN HIBAH KEPADA ANAK DIBAWAH UMUR DAN AKIBAT HUKUMNYA SETELAH ANAK MENJADI DEWASA DITINJAU DARI HUKUM PERDATA - IRA EWITA (PREMISE LAW JURNAL, 2015)
Hibah (gift) is regulated in Article 1666 of the Civil Code. It is an agreement in which a donor gives an object freely to someone, without being able to withdraw it. In the civil law, the receiver can be anyone although there are some exceptions like a minor (under-aged child). This child is considered to have no right to give or receive a hibah. When a hibah is intended to be given to a minor who is still taken care by his parents, it has to be received by his parents, whereas a hibah which is intended to be given to a minor who is still under the custody or under the amnesty, it has to be received by his guardian or by someone who is authorized by the District Court, and it is regarded as valid although the donor has already died before the authority is given. The Civil Code does not state clearly about the requirements for a hibah. However, from Article 1666 of the Civil Code, it can be concluded that some requirements for a hibah are as follows: it has to be an agreement, a donor, a receiver, and the object of hibah itself. The giving of hibah must not cause the heir(s) to be absent from the inheritance of the donor since it must not reduce or eliminate the inheritance and the legitimate portion of the heir(s). When the distribution or the giving of a hibah harms a legitimate heir, he can file as complaint about canceling it. But, when the receiver has bad faith toward the donor, the latter can withdraw it. It is recommended that legal practitioners should fully understand the system of giving a hibah and provide education in order that giving a hibah does not violate the law and harm the heir(s). It is necessary to have legal provisions which regulate the system of giving a hibah to ethnic and religious groups so that there will be legal certainty in implementing a hibah. Besides that, the prevailing legal provisions should be in a written form and enacted so that everyone and every legal practitioner understand what a hibah really is; moreover, affirmation in a clause should be transparent and clear. Keywords: Giving a Hibah, Minor, Civil La